GAMBARAN PENGGUNAAN ANTIBIOTIK INTRAVENA PADA RUANG INTENSIVE CARE UNIT (ICU) RUMAH SAKIT UNIVERSITAS ANDALAS PADANG PERIODE JANUARI-JULI 2023 - Riki Nova; Mardatillah, Mardatillah; Dessy Abdullah (Nusantara Hasana Journal, 2024)
Infectious diseases are still a major public health problem, especially in developing countries. Antibiotic resistance is still a public health problem. The Intensive Care Unit (ICU) is a special service facility in a hospital in the intensive care category that provides comprehensive and continuous services 24 hours a day. The clinical condition of intensive care inpatients generally requires intravenous drug therapy. Intravenous drug administration requires a complex procedure and requires special conditions for its preparation. Intravenous drug administration is often used in hospitals because it is important for patients who require rapid pharmacological effects or if there are patients who cannot receive or use oral drug. Objective : This study aims to determine overview of the use of intravenous antibiotics in the Intensive Care Unit (ICU) of Andalas University Hospital, Padang for the period January - July 2023. This type of research is a retrospective descriptive study with a cross sectional design using secondary data. The number of research respondents was 74 people. Methods : Data collection used medical records. Data analysis was carried out using the Statistical Product and Service Solutions (SPSS) program. Results : The majority of intravenous antibiotics in the Intensive Care Unit (ICU) at Andalas University Hospital in Padang for the period January – July 2023 were women (53.4%) with an age range of 60 years and over (33.4%) using cephalosporins (41.1%). The use of intravenous antibiotics based on the type of antibiotic used in Intensive Care Unit (ICU) patients at Andalas University Hospital in Padang for the period January – July 2023 is ceftriaxone (27.4%), and the most widely used ampoule is 2 ampoules with a percentage of (52.1%), the duration of administration of intravenous antibiotics to patients in the Intensive Care Unit (ICU) at Andalas University Hospital in Padang for the period January – July 2023 is at most 1 day with a percentage of (20%). Conclusion : The majority of intravenous antibiotics in the Intensive Care Unit (ICU) at Andalas University Hospital, Padang for the period January – July 2023 use cephalosporins.